Habitat characteristics around dens in female brown bears with cubs are density dependent - Uzal, A.; Martínez-Artero, J.; Ordiz, A.; Zarzo-Arias, A.; Penteriani, V. (Mammal Research, 2022)
The mechanisms determining habitat use in animal populations have important implications for population dynamics, conservation, and management. Here, we investigated how an increase in annual numbers of brown bear females with cubs of the year (FCOY) in a growing, yet threatened population, could explain differences in the habitat characteristics around reproductive dens. Habitat characteristics around FCOY dens were compared between a low bear density period (1995–2005) and a period when the population was increasing (2006–2016). We also compared the distance to the nearest breeding area and to all other breeding areas observed during the same year. The results suggested that during the second period, breeding areas were closer to rivers, fruit trees, and anthropogenic sources of disturbance (trails, highways) than in 1995–2005. There were also shorter distances to the closest neighboring breeding area, while the mean distance among FCOY breeding areas increased as the population grew and expanded at the landscape level. These changes may reflect that the best den locations were increasingly occupied (i.e., ideal-despotic distribution), and may be further explained by the avoidance of conspecifics by FCOY in a critical time of the year, when newborn cubs are most vulnerable. We suggest that both density-dependent factors and human-related features of the landscape are crucial to understanding long-term dynamics in the habitat use of a threatened species. V.P. and A.O. were financially supported by the I + D + I Project PID2020-114181 GB-I00 financed by the Spanish Ministry of Science and Innovation, the Agencia Estatal de Investigación (AEI), and the Fondo Europeo de Desarrollo Regional (FEDER, EU). AZA was financially supported by a Margarita Salas contract financed by the European Union-NextGenerationEU, Ministerio de Universidades y Plan de Recuperación, Transformación y Resiliencia, through the call of the Universidad de Oviedo (Asturias). Peer reviewed